Single‐Cell Sampling: Sampling from Single Cells (Small Methods 3/2018). Issue 3 (9th March 2018) - Actis, Paolo
Abstract : The cell is the fundamental unit of life. In article number1700300, Paolo Actis reviews nanoprobe‐based methods for extracting the content of living cells without affecting their viability, and paints a picture of the innovative methods that are introducing single‐cell biopsy as a way to repeatedly interrogate single living cells over time, thus enabling the dynamic study of the cell's genetic make‐up, rather than a snapshot at a particular point in time.